Impaired base excision repair is related to the pathogenesis of non-alcoholic fatty liver disease - Ziółkowska, Sylwia; Czarny, Piotr; Szemraj, Janusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2020)
Non-alcoholic fatty disease (NAFLD) is a liver disorder that affects up to 30% of the population, mainly in Western countries. It is estimated that up to 75% of NAFLD patients will develop a more aggressive form of the disease, non-alcoholic steatohepatitis (NASH). NAFLD can lead to fibrosis and liver failure; however, it is difficult to diagnose NAFLD due to its non-specific symptoms. Unfortunately, there is no treatment available for this disease. The risk factors of NAFLD are obesity and insulin resistance (IR). The molecular factors that seem to play an important role in the pathogenesis of NAFLD are oxidative stress as well as impaired DNA damage repair processes; a great body of evidence confirms an association with the base excision repair (BER) pathway. The activity of BER is decreased in patients with NAFLD and in animal models of this disease. In order to better understand the underlying basis of the disease, knowledge should be broadened in the area of DNA repair in NAFLD.